Polypyrrole Modified E-Coat Paint for Corrosion Protection of Aluminum AA1200 - Contri, Giseli; Zimmermann, Camila Aparecida; Ramoa, Sílvia Daniela Araújo Da Silva; Schmitz, Débora Pereira; Ecco, Luiz Gustavo; Barra, Guilherme Mariz de Oliveira; Fedel, Michele (Frontiers in Materials, 2020)
This article reports the potential of Polypyrrole (PPy) particles as anticorrosive additive on an epoxy water-based paint to increase the corrosion protective property of aluminum-coated panels. AA1200 aluminum panels were painted using the electrophoretic deposition method and the coatings with different concentrations of PPy particles tested. PPy particles were synthetized by oxidative polymerization of pyrrole (Py) with iron (III) chloride hexahydrate (FeCl3.6H2O) in the presence of dodecylbenzenesulfonic acid (DBSA). Electrically conducting PPy particles (6.5 S.cm-1) were obtained with a size average of 154 nm. The as-prepared PPy particles were added into a water-based epoxy paint and AA1200 panels were coated via electrophoretic deposition method. The corrosion protective properties of e-coated AA1200 panels were evaluated by means of electrochemical impedance spectroscopy over prolonged exposure time in neutral non-aerated 0.1 M NaCl electrolyte. In particular, the addition of 0.4 wt. % PPy has improved the coating corrosion protective property with respect to epoxy clearcoat and exhibited the highest value among the studied coatings.